Antibody banding patterns of the enzyme-linked immunoelectrotransfer blot and brain imaging findings in patients with Neurocysticercosis. - Pretell, Edwin Javier (2018)
Background. The enzyme-linked immunoelectrotransfer blot (EITB) assay is the reference serological test for neurocysticercosis (NCC). A positive result on EITB does not always correlate with the presence of active infections in the central nervous system (CNS), and patients with a single viable brain cyst may be EITB negative. Nonetheless, EITB antibody banding patterns appears to be related with the expression of 3 protein families of Taenia solium, and in turn with the characteristics of NCC in the CNS (type, stage, and burden of viable cysts). Methods. We evaluated EITB antibody banding patterns and brain imaging findings of 548 NCC cases. Similar banding patterns were grouped into homogeneous classes using latent class analysis. The association between classes and brain imaging findings was assessed. Results. Four classes were identified. Class 1 (patients negative or only positive to the GP50 band, related to the protein family of the same name) was associated with nonviable or single viable parenchymal cysticerci; class 2 (patients positive to bands GP42–39 and GP24, related to the T24-42 protein family, with or without anti-GP50 antibodies) was associated with intraparenchymal viable and nonviable infections; classes 3 and 4 (positive to GP50, GP42-39, and GP24 but also responding to low molecular weight bands GP21, GP18, GP14, and GP13, related to the 8 kDa protein family) were associated with extraparenchymal and intraparenchymal multiple viable cysticerci. Conclusions. EITB antibody banding patterns correlate with brain imaging findings and complement imaging information for the diagnosis of NCC and for staging NCC patients.